ANALYSIS OF THE RELATIONSHIP BETWEEN ANTHOPOMETRIC STATUS AND ENVIRONMENTAL FACTORS ON THE INCIDENCE OF ACUTE RESPIRATORY TRACT INFECTION - Mariana Mariana Mariana (Majalah Kedokteran Sriwijaya, 2021)
ABSTRACTAcute respiratory tract infection (ARI) is a form of infection in the respiratory tract that can interfere with respiratory function. Apart from being influenced by the environment, ARI is also influenced by host factors such crowded living quarters, malnutrition, incomplete immunization and economic status. Based on the high incidence, morbidity and mortality due to acute respiratory infections, it is necessary to control risk factors to prevent the incidence of ARI. This study will assess the relationship between anthropometric status and home environmentalfactors on ARI in Palembang City. This research is an observational analytic study with cross sectionaldesign. The research was conducted by distributing using a questionnaire. The data obtained were then analyzed using SPSS. From 123 respondents, it was found that most of the respondents were 25-59 months old (59.3%) and male (51.2%). There were 14.6% of children under five years old with abnormal anthopometric status and 65.0% of respondents had a good home environment score. 70.7% of all respondents suffer from ARI. From 70% of respondents who suffered from ARI, it was found that 71.4% were male under five years old, 88.9% were under-five years old with abnormal anthopometric status which was divided into under nutrition and over nutrition anthopometric status, and 71.3% had a score good home environment. From the results of the chi-square test, the p value of ARI incidence was 0.048 with OR 3.8 (95% CI: 0.8-17.6) which indicated that there was a significant relationship (p <0, 05) anthopometric status and the incidence of ARI in children under five years old. The Kruskal Wallis test results showed that the p value of ARI incidence was 0.978 which indicated that there was no significant relationship (p> 0.05) the home environment score and the incidence of ARI in children under five years old. This study found a significant relationship between anthopometric status and the incidence of ARI and did not find a significant relationship between home environmental scores and the incidence of ARI.